PENGARUH JOB CRAFTING TERHADAP INNOVATIVE WORK BEHAVIOR DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI DALAM PERSPEKTIF ETIKA BISNIS ISLAM (STUDI PADA KARYAWAN PT DIMITRA ADI WIJAYA) - Amalia, Putri Nur; Sanjaya, Vicky F; Devi, Yulistia (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of Job Crafting on Innovative Work Behavior of employees with Work Engagement as a mediating variable at PT Dimitra Adi Wijaya Properti Lampung. The background of this study is based on the important role of human resources in achieving organizational goals, where innovative behavior is a crucial factor. The research method used is quantitative with a descriptive approach. The sampling technique uses saturated sampling with a total of 78 employees as respondents. Data were analyzed using the Partial Least Square (PLS) method. The results of the study indicate that Job Crafting has a positive and significant effect on Innovative Work Behavior. In addition, Job Crafting has a positive and significant effect on Work Engagement. The next result shows that Work Engagement has a positive and significant effect on Innovative Work Behavior. It is known that Work Engagement partially mediates the relationship between Job Crafting and Innovative Work Behavior.